Penerapan representasi visual menggunakan komik sebagai upaya meningkatkan kemampuan berpikir kritis dan penguasaan konsep siswa pada materi sistem saraf - Rahmi, Nisrina Nur; Purwianingsih, Widi; Sriyati, Siti (Assimilation: Indonesian Journal of Biology Education, 2021)
The purposes of this research were to analyze the application of visual representations using comics as an effort to improve student’s critical thinking skills and mastery of concepts in nervous system material. The subject of this study is second grade-students in Senior High School. The method used in this research is Quasi experimental. The results of student’s critical thinking skills have increased higher in the experimental class, although the results of the critical thinking skills of the two classes are in the moderate category, the results of critical thinking in the experimental class showed that the increase in N-Gain was higher with N-Gain = 0.64 (medium category) while N-Gain in the control class = 0.53 (medium category). The results mastery of concepts in experimental class have n-gain is higher the n-gain control class with n-gain is 0.71 (high category), and the control class n-gain is 0.53 (medium category). The results of student responses showed that the majority of students were interested in using comic visual representations of 83.33%. Therefore it can be concluded that the use of comics can improve thinking skills and mastery of concepts better.